Beyond Monopoly : Globalization and Contemporary Italian Media. - (EDITORS), ARDIZZONI/FERRARI (Rowman & Littlefield Pub. Group, 2010)
Current trends of globalization have influenced the social, economic, and political framework of national media worldwide. In recent years, the field of media studies has focused on globalization as a phenomenon that has greatly impacted the production and reception of media formats. By reshaping local economies, diversifying societies, and introducing digital technologies, the globalization of media has enacted a process of re-definition of national and local broadcasting. Beyond Monopoly: Globalization and Contemporary Italian Media examines the impact of globalization on contemporary Italia.